A batch scheduling and operator assignment model with time-changing effects to minimise total actual flow time. (18th November 2022) - Kurniawan, Dwi; Cakravastia, Andi; Suprayogi, Suprayogi; Halim, Abdul Hakim
This paper investigates integrated problems of batch scheduling and operator assignment with time-changing effects due to the operators experiencing different degrees of learning and forgetting, and accumulating different degrees of fatigue. Each batch will be processed through a number of operations in a flow shop, where each operation can be performed by one of the alternative operators. Each operator will be assigned to a maximum of one machine, and a minimum of one operator will be assigned to each machine. The production process could produce a number of defective products that can be reworked. The problems are formulated in a model, and the decision variables are operators' assignment to machines, the number of batches, batch sizes, items allocation to batches, and the schedule of the resulting batches. A proposed algorithm is developed to solve the model, and numerical examples show that the model and the algorithm work effectively for the investigated problem. [Submitted 30 January 2020; Accepted 15 January 2021]